1×sinx^2-cos^2x

3 answers

= sinx^2 - cos^2x

This expression cannot be further simplified as it is already in its simplest form.
well, sinx^2 - cos^2x = -cos(2x)
Yes, that's correct.

sinx^2 - cos^2x can be rewritten as -cos(2x) using the double angle identity for cosine.

So, 1×sinx^2-cos^2x = -cos(2x).
Similar Questions
  1. Prove the following:[1+sinx]/[1+cscx]=tanx/secx =[1+sinx]/[1+1/sinx] =[1+sinx]/[(sinx+1)/sinx] =[1+sinx]*[sinx/(sinx+1)]
    1. answers icon 3 answers
    1. answers icon 3 answers
  2. Simplify sin x cos^2x-sinxHere's my book's explanation which I don't totally follow sin x cos^2x-sinx=sinx(cos^2x-1)
    1. answers icon 1 answer
  3. Hello! Can someone please check and see if I did this right? Thanks! :)Directions: Find the exact solutions of the equation in
    1. answers icon 1 answer
more similar questions